2019
DOI: 10.1177/2150135119862598
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Cardiopulmonary Resuscitation (ECPR) in Infants and Children: A Single-Center Retrospective Study

Abstract: Background: Extracorporeal cardiopulmonary resuscitation (ECPR) is increasingly used to rescue patients with cardiac arrest refractory to conventional therapy, necessitating evaluation of factors that may affect outcomes. Methods: A single-center retrospective review of pediatric patients (<21 years old) who underwent ECPR from January 2010 to November 2017. Comparisons between nonsurvivors and survivors, to decannulation and discharge, were made. Factors associated with survival and rate of complications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
0
19
1
Order By: Relevance
“…Previous studies have shown that renal and neurological injury, as part of post-arrest multi-organ dysfunction, are important predictors for poor outcomes in children undergoing extracorporeal cardiopulmonary resuscitation. 3,4,6,19,21,30 We did not find a relationship between abnormal neuroimaging during extracorporeal membrane oxygenation and mortality in our cohort; however, abnormal pupillary response had a significant strong correlation with poor outcome.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Previous studies have shown that renal and neurological injury, as part of post-arrest multi-organ dysfunction, are important predictors for poor outcomes in children undergoing extracorporeal cardiopulmonary resuscitation. 3,4,6,19,21,30 We did not find a relationship between abnormal neuroimaging during extracorporeal membrane oxygenation and mortality in our cohort; however, abnormal pupillary response had a significant strong correlation with poor outcome.…”
Section: Discussioncontrasting
confidence: 68%
“…Many prior studies of extracorporeal cardiopulmonary resuscitation include patients with wide ranges of duration of chest compressions prior to cannulation, some of them including patients receiving less than 10 minutes of cardiopulmonary resuscitation prior to placement on mechanical support. 2,6,11,12,[18][19][20][21][22][23][24][25][26][27][28][29][30] Our focus on those patients receiving prolonged cardiopulmonary resuscitation provides information about a more discrete and potentially higher risk population. We focused on patients with primary cardiac disease because prior studies demonstrated increased survival with extracorporeal cardiopulmonary resuscitation and conventional cardiopulmonary resuscitation compared to non-cardiac patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is an active effort to issue an early warning of changes in a patient's condition by scoring blood pressure, pulse, respiratory rate, body temperature, oxygen saturation, and level of consciousness. 52 The use of a pediatric early warning score has reduced the incidence of cardiac arrest, length of stay in the hospital, and mortality as well as unplanned transfer to the pediatric intensive care unit. 53,54 However, there are not many studies on the frequency of early response as per the working hours of the rapid response team (RRT) and the patient's prognosis, and there is currently no consensus on the standard for activating the domestic RRT; therefore, continuous further study is required.…”
Section: Rapid Response System For Preventing Pediatric Cardiac Arrestmentioning
confidence: 99%